Southern right whale dolphins from Tasmania - Woehler, E; Ward, C (2015)
A beach-washed carcass of a southern right whale dolphin ( Lissodelphis peronii ) in December 2013 was the ninth confirmed stranding record from Tasmania. Details of the carcass are presented, and all previous records from Tasmania tabulated for the first time. A seasonal pattern in records may be present, with the majority of records being from winter to early spring, possibly indicative of migration past Tasmania.